2008
DOI: 10.1007/s00417-008-0944-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of non-adherence to topical hypotensive treatment in Dutch glaucoma patients

Abstract: Non-adherence to topical glaucoma medication is fairly common. Aids that minimize forgetfulness and delivery systems facilitating the delivery of medications to the eye could be considered to enhance patient adherence before advancing to other therapies with additional risks and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
3
13

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 42 publications
5
26
3
13
Order By: Relevance
“…Assessment of drop administration skills may assist in more accurately assessing patients' ability to adhere to a drop regimen. 20 We found that there was very little ongoing reinforcement with regard to adherence issues for followup patients. A Chinese study that compared knowledge between two cohorts found that patients who received ongoing support through membership of a glaucoma club were more knowledgeable about their disease than those who did not have this support.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Assessment of drop administration skills may assist in more accurately assessing patients' ability to adhere to a drop regimen. 20 We found that there was very little ongoing reinforcement with regard to adherence issues for followup patients. A Chinese study that compared knowledge between two cohorts found that patients who received ongoing support through membership of a glaucoma club were more knowledgeable about their disease than those who did not have this support.…”
Section: Discussionmentioning
confidence: 80%
“…Studies involving patients with chronic diseases, such as diabetes 51 and HIV, 52 found that poor adherence arose as patients had difficulties changing their lifestyle to integrate a therapeutic regimen. As we also found, forgetfulness is frequently cited as a reason for poor adherence 20,37,[53][54][55] ; an intervention incorporating reminder systems into daily activities may prove advantageous.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Nearly half of patients in one study indicated that they required more information on the correct administration of eye drops. (Olthoff et al, 2009) Successfully improving adherence will likely require a multipronged approach that is individually tailored for each patient. Several recommendations have been made to overcome the different potentialities for nonadherence.…”
Section: Methods For Improving Adherencementioning
confidence: 99%
“…taraf›ndan gerçeklefltirilen bir çal›flmada hastalar, glokom hakk›nda kendilerine verilecek e¤itim ve daha basit bir tedavi protokolü sayesinde tedaviye uyumlar›n›n artaca¤›n› ifade etmektedirler (21). Kullan›lan ilaç say›-s›n›n THU üzerindeki olumsuz etkisi yap›lan çal›flmalarla ortaya konmufltur (22)(23)(24)(25). Tedaviye eklenen ilaçla sa¤lanacak G‹B düflüflü yan›nda hastan›n tedaviye olan uyumunda oluflabilecek bozulmalar dikkate al›nmal›d›r.…”
Section: Tart›flmaunclassified